USING SEQUENCE SIGNAL WORDS TO IMPROVE X SCIENCES STUDENTS’ ABILITY IN WRITING A NARRATIVE AT SMA SUNAN KALIJOGO JABUNG - Muhsin Abdul Hamid (Language-Edu, 2021)
The researcher used a Classroom Action Research (CAR). This classroom action research was done at class X Sciences SMA sunan kalijogo jabung. Subject in this research was 25 students’. The instrument used to collect the data was observation checklist and test. The research consisted two cycles where each cycle concerned of three meetings. The researcher findings indicated that the use of Sequence signal words in writing narrative text was able to improve the students’ writing skill based on the three aspects. Equally important, the successful indicators which needed to be reached by the students significantly increased. From the pre-cycle test, there were 6 students successful and the students who fail. But, when the first cycle finished, the students who fail significantly decreased to 10 students only. It meant that, successful indicators increased three times after the researcher did it. Keywords: Sequence Signal Words, Writing, Narrative.